Faktor-faktor Yang Mempengaruhi Pengungkapan Lingkungan Pada Perusahaan BUMN Dan BUMS - Hafid Nur Hidayat; Christiyaningsih Budiwati (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2019)
The purposes of this research is to analyze factors that affect environtmental disclosure to SOE and POE during 2014-2017. There are several factors that affect the environmental disclosure of the company. These factors are environmental performance, profitability, leverage, ROA, and firm size. The sample used was 46 companies that listed in Indonesia Stock Exchange during 2014–2017 with several selection criteria. This research used multiple regression analysis. The result shows that environmental performance and firm size has positive effect in SOE and POE environmental disclosure. While profitability, leverage, and ROA has negative effect in SOE and POE environmental disclosure.